THE CONSTRAINTS OF THE IMPLEMENTATION OF TEAM-BASED LEARNING IN CLASSROOM ACTION RESEARCH CLASS - Rusiana, Rusiana (Faculty of Education and Teacher Training, Universitas Islam Negeri Walisongo Semarang, 2016)
The previous research that I conducted, the use of Team-Based Learning in Classroom Action Research (CAR) class is well accepted and gives a good inï¬‚uence on the studentsâ€™ learning. To have a responsibility to teach Action Research and to keep being reï¬‚ective as a teacher, I am interested to implement TbL in anoth- er class of CAR which is aimed at knowing the constraints of its implementation and how the students cope with those constraints. The design of the research is qualitative research. The participants are one class ofÂ Classroom Action Research class consists of Â 16 students. The instruments are observation and questionnaires. The ï¬ndings show that the constraints on the implementation of TbL in CAR class are dealing with the material, team work, and incomplete team member. To cope with the constraints, the students have dis- cussion and ask for opinions among the team member. In addition, instead of discussion, to have complete team member is the pos- sible solution to cope with the constraints.